LAGU ANAK SEBAGAI MEDIA DALAM PENANAMAN KARAKTER ANAK USIA DINI - , Ernawati; , Meinita; Ekayanti Tarigan (Yayasan Pendidikan Internasional Bengkulu, 2022)
The formation of early childhood character is an important effort that must be carried out by Kindergarten level teachers. Character building from an early age is expected to be an important provision for children to grow according to the child's emotional development. Education is not only aimed at producing students who are cognitively intelligent but also to shape children's emotional intelligence so that they become students with good character. This research is a solution to the formation of early childhood character through stimulating children's songs that contain character values ​​in them. This study uses a qualitative descriptive approach to achieve the research focus. A collection of children's songs is the object of this research with the titles: four magic words, before we eat, and oh mom and dad. Children's songs which are the object of research are analyzed to classify the character values ​​contained in the songs implicitly. The results of the study show that the character values ​​obtained include: noble character, hard work, responsibility, independence, cooperation, caring, and cooperation.